Measuring Undergraduates’ Motivation Levels When Learning to Program in Virtual Worlds - Vergara Villegas, Osslan Osiris (2024)
Teaching/learning programming is complex, and conventional classes often fail to arouse students’ motivation in this discipline. Therefore, teachers should look for alternative methods for teaching programming. Information and communication technologies (ICTs) can be a valuable alternative, especially virtual worlds. This study measures the students’ motivation level when using virtual worlds to learn introductory programming skills. Moreover, a comparison is conducted regarding their motivation levels when students learn in a traditional teaching setting. In this study, first-semester university students participated in a pedagogical experiment regarding the learning of the programming subject employing virtual worlds. A pre-test-post-test design was carried out. In the pre-test, 102 students participated, and the motivation level when a professor taught in a traditional modality was measured. Then, a post-test was applied to 60 students learning in virtual worlds. With this research, we have found that the activity conducted with virtual worlds presents higher motivation levels than traditional learning with the teacher. Moreover, regarding gender, women present higher confidence than men. We recommend that teachers try this innovation with their students based on our findings. However, teachers must design a didactic model to integrate virtual worlds into daily teaching activities.